Learn more about

Refine search

Results (displaying matches 1-50 of 1130) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
3319.a.3319.1 3319.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^4 + x^3\) $\mathrm{USp}(4)$ 2
3391.b.3391.1 3391.b \(y^2 + (x^3 + x + 1)y = -x^5 - x^4\) $\mathrm{USp}(4)$ 2
3721.a.3721.1 3721.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 + 3x^2 + x\) $E_6$ 2
4021.a.4021.1 4021.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^2 + x\) $\mathrm{USp}(4)$ 2
4356.b.470448.1 4356.b \(y^2 + x^3y = -x^4 - 6x^3 + 22x^2 - 24x + 9\) $\mathrm{USp}(4)$ 1
4673.a.4673.1 4673.a \(y^2 + x^3y = x^3 - x^2 - x + 1\) $\mathrm{USp}(4)$ 2
4925.b.4925.1 4925.b \(y^2 + x^3y = -x^4 - x^3 + x + 1\) $\mathrm{USp}(4)$ 2
5113.a.5113.1 5113.a \(y^2 + (x^2 + x + 1)y = x^6 - 2x^4 - x\) $\mathrm{USp}(4)$ 2
5209.a.5209.1 5209.a \(y^2 + (x^3 + x + 1)y = x^4 + x^3 - x^2 - x\) $\mathrm{USp}(4)$ 2
5414.a.10828.1 5414.a \(y^2 + (x^3 + 1)y = 2x^2 + x\) $\mathrm{USp}(4)$ 2
5449.b.5449.1 5449.b \(y^2 + (x^3 + x + 1)y = x^4 + 2x^3 + x^2\) $\mathrm{USp}(4)$ 2
5476.b.21904.1 5476.b \(y^2 + y = x^6 - x^2\) $G_{3,3}$ 2
5501.a.5501.1 5501.a \(y^2 + (x^3 + x^2 + 1)y = -2x^3 - 3x^2 + x + 2\) $\mathrm{USp}(4)$ 2
5599.a.5599.1 5599.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^2 - 2x\) $\mathrm{USp}(4)$ 2
5618.a.11236.1 5618.a \(y^2 + (x^3 + 1)y = -x^5 + x^4 + x^2 - x\) $G_{3,3}$ 2
5641.a.5641.1 5641.a \(y^2 + y = x^6 - x^5 - x^4 + 2x^3 - x\) $\mathrm{USp}(4)$ 2
5705.a.5705.1 5705.a \(y^2 + (x^3 + 1)y = x^5 + x^4 + x^3 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 2
5911.b.5911.1 5911.b \(y^2 + (x^3 + x + 1)y = -2x^4 + x^3 - x^2\) $\mathrm{USp}(4)$ 2
6229.a.6229.1 6229.a \(y^2 + (x^3 + x + 1)y = -2x^4 + 3x^3 - 3x^2\) $\mathrm{USp}(4)$ 2
6463.a.6463.1 6463.a \(y^2 + (x^2 + x + 1)y = x^6 - x^4\) $\mathrm{USp}(4)$ 2
6511.a.6511.1 6511.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^4 - 2x^2 - x\) $\mathrm{USp}(4)$ 2
6718.a.13436.1 6718.a \(y^2 + (x^2 + x + 1)y = x^6 + x^5 - x^2 - x\) $\mathrm{USp}(4)$ 2
6869.a.6869.1 6869.a \(y^2 + (x^2 + x + 1)y = x^6 - x^4 - x^2 - x\) $\mathrm{USp}(4)$ 2
7165.a.7165.1 7165.a \(y^2 + (x^3 + 1)y = x^4 + x^3 - 2x^2\) $\mathrm{USp}(4)$ 2
7225.a.36125.1 7225.a \(y^2 + (x^3 + 1)y = -x^5 + 2x^4 - 3x^2 - x\) $G_{3,3}$ 2
7396.a.29584.1 7396.a \(y^2 + y = x^6 - 2x^4 + x^2\) $G_{3,3}$ 2
7442.a.14884.1 7442.a \(y^2 + (x^3 + 1)y = x^4 + x^3 + x^2\) $G_{3,3}$ 2
7945.c.198625.1 7945.c \(y^2 + (x^3 + x + 1)y = -5x^4 + 3x^3 + 7x^2 + 2x\) $\mathrm{USp}(4)$ 2
8091.a.24273.1 8091.a \(y^2 + (x^3 + x + 1)y = -x^4 - x^2 - 2x + 2\) $\mathrm{USp}(4)$ 2
8281.b.405769.1 8281.b \(y^2 + (x^3 + x + 1)y = -3x^5 + 9x^4 - 7x^3 - 2x^2 + x\) $E_6$ 2
9093.b.63651.1 9093.b \(y^2 + (x^3 + 1)y = 2x^5 + 3x^4 + x^3 - x\) $\mathrm{USp}(4)$ 2
9309.a.27927.1 9309.a \(y^2 + x^3y = x^4 - x^2 - x + 1\) $\mathrm{USp}(4)$ 2
9331.a.9331.1 9331.a \(y^2 + x^3y = 4x^3 + 8x^2 + 5x + 1\) $\mathrm{USp}(4)$ 2
9496.a.18992.1 9496.a \(y^2 + x^3y = -x^4 - 2x^3 + 2x + 1\) $\mathrm{USp}(4)$ 2
9532.a.38128.1 9532.a \(y^2 + y = x^6 - 2x^5 - x^4 + x^2 + x\) $\mathrm{USp}(4)$ 2
9565.a.9565.1 9565.a \(y^2 + (x^3 + x^2 + x)y = -x^4 - 2x + 1\) $\mathrm{USp}(4)$ 2
10345.c.51725.1 10345.c \(y^2 + x^3y = 2x^3 + 2x^2 + x + 1\) $\mathrm{USp}(4)$ 2
10839.a.32517.1 10839.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^4 + x^3 + 2x^2\) $\mathrm{USp}(4)$ 2
10952.a.21904.1 10952.a \(y^2 + y = x^6 - 3x^4 + 2x^2\) $G_{3,3}$ 2
11011.b.77077.1 11011.b \(y^2 + x^3y = x^5 + x^4 + 2x^3 + 6x^2 + 3x - 1\) $\mathrm{USp}(4)$ 2
11011.b.143143.1 11011.b \(y^2 + x^3y = x^4 - 4x^3 + 3x^2 - x + 1\) $\mathrm{USp}(4)$ 2
11012.a.22024.1 11012.a \(y^2 + (x^3 + x^2 + 1)y = x^4 - 2x^2 - x\) $\mathrm{USp}(4)$ 2
11113.a.11113.1 11113.a \(y^2 + (x^3 + 1)y = x^4 + x^3 - x\) $\mathrm{USp}(4)$ 2
11199.b.100791.1 11199.b \(y^2 + x^3y = x^3 + x^2 - x + 1\) $\mathrm{USp}(4)$ 2
11236.a.44944.1 11236.a \(y^2 + (x^3 + x)y = -x^2 + 1\) $G_{3,3}$ 2
11271.b.912951.1 11271.b \(y^2 + x^3y = 3x^3 + 7x^2 + 7x + 3\) $\mathrm{USp}(4)$ 2
11383.a.11383.1 11383.a \(y^2 + (x^3 + 1)y = -x^4 + 2x^3 - x\) $\mathrm{USp}(4)$ 2
11565.a.34695.1 11565.a \(y^2 + x^3y = -2x^4 - x^3 + 7x^2 - 5x + 1\) $\mathrm{USp}(4)$ 2
11705.a.11705.1 11705.a \(y^2 + (x^3 + 1)y = -x^4 + x^3 + 2x^2 - 2x\) $\mathrm{USp}(4)$ 2
11708.a.23416.1 11708.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 - 2x\) $\mathrm{USp}(4)$ 2
Next

Download all search results for